Engels tentang Evolusi Manusia: Catatan Pendahuluan atas Gagasan Friedrich Engels (1820-1895) tentang Alur Evolusi Manusia dan Peran Kerja di Dalamnya - Dede Mulyanto (Antropologi Indonesia, 2011)
This paper represents Engels’ theory of human origin with more modern facts and theories from contemporary fossil record. In Engels’ theory, brain and cognitive ability is not the essential attribute of humanity. Brain capacity is not a cause; it is result or effect of evolution of more essential attribute in hominid evolution, that are terrestrial-bipedal life style and the use of tools by which labour social organisation emerge in hominid evolution. Keywords: evolution, paleoanthropology, Marxism, hominid